2011
DOI: 10.1021/ac202170e
|View full text |Cite
|
Sign up to set email alerts
|

Sprouting Angiogenesis under a Chemical Gradient Regulated by Interactions with an Endothelial Monolayer in a Microfluidic Platform

Abstract: Microfluidic cell culture assays are versatile tools for studying cell migration, particularly angiogenesis. Such assays can deliver precisely controlled linear gradients of chemical stimuli to cultured cells in a microfluidic channel, offering excellent optical resolution and in situ monitoring of cellular morphogenesis in response to a gradient. Microfluidic cell culture assays provide a chemical gradient subject to molecular diffusion, although cellular metabolism can perturb it. The actual gradient perturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 42 publications
1
86
0
Order By: Relevance
“…[11][12][13][14][15] To verify that the device design with non-straight pillars allows the formation of a concentration gradient within the central channel, we performed preliminary numerical simulations in COMSOL. Generally, the generation and maintenance of a stable concentration gradient between the source and the sink depend on the diffusion coefficient of the diffusing molecule within the hydrogel, as well as on the geometrical features of the device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15] To verify that the device design with non-straight pillars allows the formation of a concentration gradient within the central channel, we performed preliminary numerical simulations in COMSOL. Generally, the generation and maintenance of a stable concentration gradient between the source and the sink depend on the diffusion coefficient of the diffusing molecule within the hydrogel, as well as on the geometrical features of the device.…”
Section: Resultsmentioning
confidence: 99%
“…Different devices based on this approach have been developed in order to study and unravel the intricate cell-signal interactions that occur in vivo. [13][14][15] Although these lFds may differ in terms of shape, dimensions, and culturing conditions, they all rely on the resistance effects of a cell laden biopolymeric gel to the flow of soluble molecules of interest. The presence of short cuts within the cell containing 3D matrix affects the spatial distribution of molecules and matrix collapse or the local densification impairs the diffusion mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Human MSCs were isolated from fresh bone marrow aspirates obtained from Cambrex Life Sciences as previously described (38,50), grown in high-glucose DMEM with 10% (vol/vol) FBS and 1% penicillin/streptomycin (all from Invitrogen) with 0.1 ng/mL basic FGF (Invitrogen), and expanded to passage 8 or lower. Human umbilical vein endothelial cells were isolated from postnatal discarded umbilical veins and fully de-identified following the protocol IRB-AAAC4839 approved by the Columbia University Institutional Review Board, and grown using EGM-2 Media (Lonza) to passage 8 or lower.…”
Section: Methodsmentioning
confidence: 99%
“…For example, endothelial cell (EC) stabilization via mesenchymal stem cell (MSC) interactions is known to facilitate the maturation of blood vessels impacting many physiologic systems, from tumors to engineered tissues (33)(34)(35). Recent studies clearly showed the importance of microscale gradients for vasculogenesis (36)(37)(38).…”
mentioning
confidence: 99%
“…23 Researchers have taken advantage of these microfluidic platforms and successfully developed in vitro models for studying various important physiological phenomena, such as wound healing, 24,25 cancer metastasis, 26,27 and vascular angiogenesis. 28,29 Among these innovative microfluidic devices, some are dedicated for co-culture system, which is a rather challenging task compared to handling a single type of cells on a chip. Prior reports have shown various designs, including valves, 30 laminar flow between immiscible liquids, 31,32 separate compartments for dynamic co-culture, 33 and detachable substrates, where the cells are individually cultured on different substrates.…”
Section: Introductionmentioning
confidence: 99%